A Copper-Catalyzed Tandem Cyclization Reaction of Aminoalkynes with Alkynes for the Construction of Tetrahydropyrrolo[1, 2-a]quinolines Scaffold. Issue 1 (December 2017) - Ma, Can-Liang; Zhao, Jin-Hao; Yang, Yong; Zhang, Min-Kui; Shen, Chao; Sheng, Rong; Dong, Xiao-Wu; Hu, Yong-Zhou
Abstract A synthetic method for diversely substituted tetrahydropyrrolo[1, 2-a ]quinolines was developed via CuCl-catalyzed cascade transformation of internal aminoalkynes with alkynes under microwave- irradiation.